- ASPEK GABUNGAN PIDANA TERHADAP PELAKU PEMERKOSAAN DAN KEPEMILIKAN SENJATA (PUTUSAN NOMOR 200/PID.SUS/2021/PN.TRG): - - Mohammad Yofarrel; Widjajanti, Ermania (Faculty of Law, Universitas Trisakti, 2023)
The defendant Cecep Sutarno was found guilty of being legally and conclusively proven to have committed the crime of rape as specified in Article 285 of the Criminal Code based on the